ATP citrate lyase inhibitor triggers endoplasmic reticulum stress to induce hepatocellular carcinoma cell apoptosis via p‐eIF2α/ATF4/CHOP axis. Issue 3 (3rd January 2021) - Zheng, Yihu; Zhou, Qingqing; Zhao, Chang; Li, Junjian; Yu, Zhengping; Zhu, Qiandong
Abstract: ATP citrate lyase (ACLY), a key enzyme in the metabolic reprogramming of many cancers, is widely expressed in various mammalian tissues. This study aimed to evaluate the effects and mechanisms of ACLY and its inhibitor BMS‐303141 on hepatocellular carcinoma (HCC). In this study, ACLY was highly expressed in HCC tissues, especially in HepG2 and Huh7 cells, but was down‐regulated in Hep3B and HCC‐LM3 cells. Besides, ACLY knockdown inhibited HepG2 proliferation and clone formation, while opposite result was noticed in HCC‐LM3 cells with ACLY overexpression. Moreover, ACLY knockdown impeded the migration and invasion abilities of HepG2 cells. Similarly, BMS‐303141 suppressed HepG2 and Huh‐7 cell proliferation. The p‐eIF2α, ATF4, CHOP p‐IRE1α, sXBP1 and p‐PERK were activated in HepG2 cells stimulated by BMS‐303141. In cells where ER stress was induced, ATF4 was involved in BMS‐303141‐mediated cell death procession, and ATF4 knockdown reduced HCC cell apoptosis stimulated by BMS‐303141. In a mouse xenograft model, combined treatment with BMS‐303141 and sorafenib reduced HepG2 tumour volume and weight. In addition, ACLY expression was associated with HCC metastasis and tumour‐node‐metastases staging. Survival analysis and Cox proportional hazards regression model showed that overall survival was lower in HCC patients with high ACLY expression; AFP level, TNM staging, tumour size and ACLY expression level were independent risk factors affecting their overall survival. In conclusion, ACLY might represent a promising target in which BMS‐303141 could induce ER stress and activate p‐eIF2α/ATF4/CHOP axis to promote apoptosis of HCC cells, and synergized with sorafenib to enhance the efficacy of HCC treatment.